2016
DOI: 10.21037/jtd.2016.03.89
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of idiopathic pulmonary fibrosis patients according to their smoking status

Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is the most common form of idiopathic interstitial pneumonias (IIPs) of unknown etiology that often affects male, elderly smokers. However, it is sometimes observed in never smokers. This study aimed to clarify the clinical characteristics of IPF in never-smoking patients compared with those in smoking patients. Methods:We retrospectively reviewed medical records, pulmonary function tests, and chest highresolution computed tomography (HRCT) scan of never-smoking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 41 publications
6
30
2
Order By: Relevance
“…Annual decline of the main physiological pulmonary parameters in our cohort of iPF patients. often encounter approximately 30% never-smoking IPF patients [17]. In our study, we confirm the male predominance with a mean age of 71 years, and 27% of the all population had never smoked.…”
Section: Hospitalizationssupporting
confidence: 85%
“…Annual decline of the main physiological pulmonary parameters in our cohort of iPF patients. often encounter approximately 30% never-smoking IPF patients [17]. In our study, we confirm the male predominance with a mean age of 71 years, and 27% of the all population had never smoked.…”
Section: Hospitalizationssupporting
confidence: 85%
“…Accurate cause of all stage III patients was never smoker remains unknown. According to our previous report, never smoker IPF patients had poor prognosis (53), therefore one possibility is never smoker IPF patients tend to have pure active fibrosis compared to smoker IPF patients. Detailed evaluation of pathological findings is interesting topic.…”
Section: Discussionmentioning
confidence: 92%
“…Among IPF patients, we previously reported that 1-year modified medical research council breathlessness scale is a useful predictor of mortality (53). In IPF patients, severe dyspnea is associated with greater consumption of body energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants were screened for breathlessness using the modified Medical Research Council (mMRC) score [16]. Participants were graded from 0 to 4 depending on breathlessness-related activities reported.…”
Section: Methodsmentioning
confidence: 99%